Exploring bat-inspired cyclic tryptophan diketopiperazines as ABCB1 Inhibitors - Koh, Javier Yu Peng (2024)
Chemotherapy-induced drug resistance remains a major cause of cancer recurrence and patient mortality. ATP binding cassette subfamily B member 1 (ABCB1) transporter overexpression in tumors contributes to resistance, yet current ABCB1 inhibitors have been unsuccessful in clinical trials. To address this challenge, we propose a new strategy using tryptophan as a lead molecule for developing ABCB1 inhibitors. Our idea stems from our studies on bat cells, as bats have low cancer incidences and high ABCB1 expression. We hypothesized that potential ABCB1 substrates in bats could act as competitive inhibitors in humans. By molecular simulations of ABCB1-substrate interactions, we generated a benzylated Cyclo-tryptophan (C3N-Dbn-Trp2) that inhibits ABCB1 activity with efficacy comparable to or better than the classical inhibitor, verapamil. C3N-Dbn-Trp2 restored chemotherapy sensitivity in drug-resistant human cancer cells with no adverse effect on cell proliferation. Our unique approach presents a promising lead toward developing effective ABCB1 inhibitors to treat drug-resistant cancers.